POTENSI PENGEMBANGAN INDUSTRI PENGOLAHAN PUPUK KOMPOS DI KOTA PEKANBARU - Riyo Hidayat; Nursiah Chalid; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Pekanbaru city which is the capital of Riau province has a population growth and high levels of economic growth and activity of rapid economic activities as well. As the center of the capital of the province of Riau, Pekanbaru is the venue for the various activities of government, education, commerce, industry, transport to the service center activities of services, which the activities are related to each other by areas other county or city. From the results of the analysis carried out through descriptive method is known that the Manufacturing Compost has the potential to be developed in the city of Pekanbaru if the terms of availability of raw materials in the form of organic waste generated by three these sources(populations,traditional markets,finaldisposal) with the availability of raw materials are very abundant. Then in terms of cost of production (Fix Cost and Variable Cost), the development of processing industries compost is also considered to have a very good chance and have economic value that is suitable to be developed seriously. And compost produced marketable high value in terms of marketing because the current agricultural sector began to gradually switch to using fertilizer made from natural (organic) one of compost as a fertilizer plant to meet consumer demand.Keywords : Waste, Processing, Compost, Industrial